PENGARUH DISKON HARGA DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN IMPULSIF SECARA ONLINE (Studi Pada Pengguna Aplikasi Steam di Kota Medan) - Marza Maulana Rughasy; Nicholas Marpaung (DFAME Digital Financial Accounting Management Economics Journal, 2023)
This research observes the annual increase in the number of Steam application account users from 2019 to 2021, attributed to users having or creating multiple accounts. Additionally, there is an increase in active in-game users during this period. The study aims to examine the influence of discounts and brand image on the Steam application on online impulsive buying decisions. The research method employed is quantitative with an associative approach, involving 100 randomly selected respondents. Data were obtained through questionnaires and literature review. The results indicate that discounts do not significantly impact impulsive buying decisions, but brand image has a significant influence. However, discounts and brand image together have an impact on impulsive buying decisions, with a correlation coefficient of 0.805 and a determination coefficient of 64.1%.